Bimetallic AgPd Nanoparticles Immobilized on Amine‐Functionalized SBA‐15 as Efficient Catalysts for Hydrogen Generation from Formic Acid. Issue 21 (27th December 2016) - Wan, Chao; Yao, Fang; Li, Xiao; Hu, Kai; Ye, Mingfu; Xu, Lixin; An, Yue
Abstract: HCOOH (FA) is considered as a potential hydrogen‐storage material. The chemically stored hydrogen in FA can be catalytically released even at room temperature, which can be utilized by polymer electrolyte membrane fuel cells (PEMFCs). However, in order to make FA a feasible hydrogen‐storage medium, it is necessary to find catalysts with superior performance that enable it to produce hydrogen under moderate conditions. Herein, for the first time to our knowledge, we report amine‐functionalized SBA‐15 (SBA‐15‐Amine)‐supported bimetallic AgPd nanoparticles with various molar ratios through a facile co‐reduction method for serve as a catalyst for the dehydrogenation reaction of FA. As indicated by the turnover frequency (TOF), the performance of these catalysts depended on their composition. Among all the prepared AgPd/SBA‐15‐Amine catalysts, Ag1 Pd9 /SBA‐15‐Amine exhibited exceedingly high activity for the dehydrogenation of FA to yield high‐quality H2 at 323 K, with a maximum TOF of 964 h −1 and 100 % selectivity. It is revealed that the catalyst exhibits stable catalytic performance after multiple usage cycles. Therefore, the catalyst we developed can be a potential candidate for prompting the widespread utilization of FA as a hydrogen‐storage material. Abstract : In this article, AgPd NPs were successfully immobilized onto the amino‐functionalized SBA‐15. The Ag1 Pd9 /SBA‐15‐Amine exhibited high activity for the dehydrogenation of FA. The turnover frequency value for the dehydrogenation of formic acid over Ag1 Pd9 /SBA‐15‐Amine is 964 h −1 at 323 K.This nanocatalyst showed good chemical stability for five cycles.